Financial Fragility dan Financial Behavior Masyarakat di Masa Pandemi Covid-19 - Murviana Koto (Jurnal Akuntansi dan Pajak, 2023)
The COVID-19 epidemic began at the end of 2019 and continues to this day. Adaptation through the new normal lifestyle is still being promoted, and this is true in terms of both lifestyle and financial behavior. Individuals or families who are financially literate are expected to behave more responsibly. Good financial behavior is supposed to assist an individual or family in avoiding financial fragility. The findings of this study show that the level of financial fragility among the residents of Medan is pretty good with just 27% of all respondents. The findings of this study also show that while the residents have a poor degree of financial literacy, their financial behaviour is pretty decent. Even the public's financial behavior after the Covid-19 outbreak appears to be improving, demonstrating that people's behaviour is very adaptable to changing circumstances. Maintaining expenditures that are not more than income, being more careful to pay bills on time, improving behavior to save more consistently, and increasing efforts to set aside funds for emergency needs are all signs of improved financial behavior